Delayed Migration of Tapered Open-Cell Design Carotid Stent: A Case Report - Il Hyung Lee; Taedong Ok; Yo Han Jung; Kyung-Yul Lee; Sang Hyun Suh (Neurointervention, 2023)
We present a case of delayed migration of an open-cell design carotid stent, which is a rare complication following carotid artery stenting (CAS). A 65-year-old patient with carotid artery stenosis underwent CAS with an open-cell stent, initially achieving successful deployment. However, 4 months later, the stent migrated and resulted in restenosis. The patient underwent balloon angioplasty and received an additional stent, leading to improved blood flow. The rarity of stent migration, particularly in the absence of risk factors, highlights the need for clinicians to be vigilant and consider early imaging follow-up for patients at risk of this complication after CAS.